Political parties, caste system and India's foreign policy - Carrusca, Natalia; Granzioli, Luis Felipe de Freitas; Nilsson, Bárbara (Fronteira: revista de iniciação científica em Relações Internacionais, 2016)
The practice of the caste system remains prohibited in India, but impacts significantly the country’s social and political structure. Electoral campaigns reflect this impact: political parties’ proposals are often directed to one or another caste, influencing voters. Elected politicians adopt policies adjusted to their party’s orientation and the issue of castes substantially affects domestic policy. Nonetheless, does it affect foreign policy? The article presents an overview of the structure and formation of the national political parties, and lays out the foreign policy orientation of each Prime Minister. In the final considerations, it is argued that there is not a comprehensible relation between the political party’s orientation on castes and ministerial approaches on foreign policy.